Formation of Bis Oxadiazole- Azo Ligands and Studying of (Spectral Analysis, Thermal Behavior, Bacterial Behavior, Chemical Properties) - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
Bis oxadiazole – azo ligands were synthesized via many chemical reactions and steps represented by reaction between diamine aromatic compound with concentration hydrochloric acid and sodium nitrite in azotation reaction as a first step , then the second step involved coupling step to yield mainly compound containing di active groups , which will react with semicarbazide in cyclization step to formation first ligand , after that preparation other ligands through various reaction like insertion reaction to yield second ligand , azotation reaction to yield third ligand and substitution reaction like fourth and fifth ligands. The prepared ligands have been identified by spectral techniques like (1H NMR , FT.IR and UV-Visible spectra) with chemical studies like thermal behavior , physical properties , TLC – Paper , and biological studying like microbial assay. Keywords: Oxadiazole, Semicarbazide, amide, Cyclization , Azo, Insertion , Thiazane.